Ukraine : First Review Under the Stand-By Arrangement, Requests for Waivers of Nonobservance of Performance Criteria, and Rephasing of Purchases Under the Arrangement; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2009)
Ukraine's economic downturn has been sharper than originally envisaged, mostly reflecting the deterioration of the external environment. The staff report examines Ukraine's first review under the Stand-By Arrangement, requests for Waivers of Nonobservance of Performance Criteria, and Rephasing of Purchases Under the Arrangement. A flexible exchange rate policy, supported by base money targets and a transparent intervention strategy, remains a key component of the program. Given balance sheet effects associated with unhedged foreign currency borrowing, the central bank stands ready to take action to avoid excessive exchange rate depreciation.